Pengembangan Media Pembelajaran Menggunakan Geogebra Classroom pada Materi Limas di Kelas VII - Adiansyah, Marta; Widiawati, Widiawati; Lismareni, Neni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop a learning product using GeoGebra Classroom on the topic of pyramids that is valid and practical for Grade VII students at SMP Muhammadiyah. The research method employed is Research and Development (R&D), adapting the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results show that the developed product is considered valid with an overall score of 84%. Practicality was assessed through student response questionnaires, with results showing 78% in the one-to-one test, 96% in the small group test, and 82% in the field test. In conclusion, GeoGebra Classroom can be used as an effective learning medium to enhance students’ understanding, creativity, and construction skills. Keywords: Development, GeoGebra Classroom, Pyramids, Learning Media